A Water‐Soluble Highly Oxidizing Cobalt Molecular Catalyst Designed for Bioinspired Water Oxidation - Su, Yun‐Fei; Luo, Wen‐Zhi; Lin, Wang‐Qiang; Su, Yi‐Bing; Li, Zi‐Jian; Yuan, Yong‐Jun; Li, Jian‐Feng; Chen, Guang‐Hui; Li, Zhaosheng; Yu, Zhen‐Tao; Zou, Zhigang (Angewandte Chemie International Edition, 2022)
Herein, we present a stable water‐soluble cobalt complex supported by a dianionic 2,2′‐([2,2′‐bipyridine]‐6,6′‐diyl)bis(propan‐2‐ol) ligand scaffold, which is a rare example of a high‐oxidation species, as demonstrated by structural, spectroscopic and theoretical data. Electron paramagnetic resonance (EPR) spectroscopy and magnetic susceptibility measurements revealed that the CoIV center of the mononuclear complex in the solid state resides in the high spin state (sextet, S=5/2). The complex can effectively catalyze water oxidation via a single‐site water nucleophilic attack pathway with an overpotential of only 360 mV in a phosphate buffer with a pH of 6. The key intermediate toward water oxidation was speculated based on theoretical calculations and was identified by in situ spectroelectrochemical experiments. The results are important regarding the accessibility of high‐oxidation state metal species in synthetic models for achieving robust and reactive oxidation catalysis. A stable water‐soluble cobalt(IV) complex supported by a dianionic 2,2′‐([2,2′‐bipyridine]‐6,6′‐diyl)bis(propan‐2‐ol) ligand scaffold is very active in the catalysis of water oxidation at an overpotential of only 360 mV at pH=6.